Treprostinil improves hemodynamics and symptoms in children with mild pulmonary hypertension awaiting heart transplantation. (19th May 2020) - Hollander, Seth A.; Ogawa, Michelle T.; Hopper, Rachel K.; Liu, Esther; Chen, Sharon; Rosenthal, David N.; Feinstein, Jeffrey A.
Abstract: Background: Treprostinil, a prostacyclin analog, is a safe and effective therapy for children with PAH; however, the use of this agent in children with mild PVR elevations related to HF, including those with SV congenital heart disease awaiting HT, is understudied. We describe the hemodynamic and symptomatic changes in pediatric patients awaiting HT treated with treprostinil. Methods: Single‐center retrospective review of all patients was listed for HT who received treprostinil during the listing period. Changes in hemodynamic and functional indices between the baseline catheterization (prior to drug initiation), and prior to HT, and patient outcomes were analyzed. Results: Among 16/17 (94%) who survived to HT, 8 (50%) were female, and 10 (63%) had SV physiology. The median age at drug initiation was 9 (IQR: 1, 14) years. The median duration of therapy prior to HT was 253 (IQR: 148, 504) days. Treprostinil significantly decreased PVR (3.8 vs 3.1 WU, P  = .03), while mLA or mPCW pressure did not change (11 vs 13 mm Hg, P  = .9). HF symptoms improved in 9/15 (60%) patients without VAD support prior to drug initiation, including 4/10 (40%) who did not receive a VAD any point while awaiting HT. Conclusions: Treprostinil may be used safely in patients with mild PAH awaiting HT, including those with SV disease. PVR falls without substantial increases in mLA/mPCW pressure. HF symptoms improve in some patients.